Maya and the Lord of Shadows - Barron, Rena (Barron, Rena. Maya and the rising dark, 2022)
War is coming. Despite everything Maya and her father have done, the veil that protects the human world is failing. The Lord of Shadows has raised an army powerful enough to challenge the orishas. And it's only a matter of time before he breaks through the veil and destroys Maya's neighborhood and the rest of the world. Maya and her friends aren't going down without a fight. She's honing her guardian powers, with the help of two new allies--her long lost guardian sister and a mysterious darkbringer (who might be a double agent). But when an attack hits close to home, Maya doesn't have any more time to prepare. She must face the Lord of Shadows or risk losing everything. With her friends--Eli, Frankie, Zeran, and Eleni--by her side, Maya leads the charge in an epic showdown that takes her across worlds and to the edge of the universe. Will she succeed or will Darkness prevail, once and for all? --